Bipartite Ulnar Nerve - A Rare Anatomical Variation - Oliveira, Marta (2022)
The diagnosis of peripheral neuropathies and motor deficits may be difficult and requires a deep knowledge of the peripheral nerves anatomy. We present an image of an elbow ultrasonography that revealed a rare anatomical variation of the ulnar nerve in a patient with symptoms compatible to an ulnar entrapment syndrome.